Distribusi dan Sex Ratio Udang Macrobrachium pilimanus pada Sungai Mengaji di Banyumas - Prodhiana Prodhiana; Moh. Husein Sastranegara; Elly Tuti Winarni (BioEksakta : Jurnal Ilmiah Biologi Unsoed, 2022)
The one forms of freshwater ecosystems which is the habitat of various organisms is rivers. The Mengaji River is a river that springs from the southern slopes of Mount Slamet. Rivers always experience changes in physical, chemical, and biological factors. The decline in river water quality greatly affects the distribution and sex ratio of Macrobrachium pilimanus in the Mengaji River. This research aims to determine the distribution and sex ratio of M. pilimanus shrimp in the Mengaji River. The research was conducted using a survey method for determining stations and purposive random sampling for sampling. The samples obtained were then identified and measured using the morphometric method. Research was conducted between June-August 2020. Shrimp distribution data were analyzed using the "F" test with SPSS 2016, while the sex ratio of shrimp was analyzed using the sex ratio formula from the Kao and Liu method. The results of this study found that the distribution of M. pilimanus shrimp in the Mengaji River, Banyumas, was not evenly distributed between stations. The highest distribution was found at Station IV, while the highest female shrimp was found at Station II. The sex ratio of M. pilimanus shrimp in the Mengaji River Banyumas was not balanced and was dominated by females. The sex ratio was found to be the highest at Station II.